Tinjauan Undang-Undang Cipta Kerja Terhadap Pembatalan Keputusan Gubernur DKI Jakarta Nomor 1517 Tahun 2021 Tentang Upah Minimum Provinsi Tahun 2022 (Studi Kasus Dalam Putusan 11/G/2022/Ptun Jkt) - Sheila, Eirene Eva Marta; Ramadhanti, Shaila Azalea; Rahman, Hafizh Aulia; Tarina, Dwi Desi Yayi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
In the Job Creation Law, minimum wage calculations are determined based on variables such as economic growth, inflation and certain indices. This research aims to review the Job Creation Law regarding the annulment of the Governor of DKI Jakarta's Decree Number 1517 of 2021 concerning the 2022 Provincial Minimum Wage. In this context, this research focuses on the implications of the Job Creation Law for the decision of the Governor of DKI Jakarta. The method that the author chose is a data collection method by means of literature study by looking for scientific reviews and using a case study approach sourced from Decision 11/G/2022/PTUN JKT. The research results show that based on the Job Creation Law the judge's decision in this case is correct, the increase has exceeded the specified regulatory limits and is detrimental to other parties, namely entrepreneurs who pay workers.